Data: an ethical overview. Issue 3 (2nd September 2017) - Shilina, Marina; Couch, Robert; Peters, Benjamin
ABSTRACT: This introduction reviews the intersection of data, ethics, and the Russian case. Its four sections, respectively, raise the ethical stakes concerning the contemporary data, outline a proverbial step toward a more humane ethics of data by normalizing certain features (such as anthropomorphic care) in the human–data relationship, reviews the leading scholarly literature on data, institutions, and social structures in specific, and summarizes the diverse contributions to this special journal issue. Each step is meant to broaden, ground, and sober the study of data in the modern moment. Taken together, the aim of this introduction, like the special issue it introduces, is to press the cutting edge of more open, humane, and critical research on data and the twenty-first century Russian case.